Absence of SCAPER causes male infertility in humans and Drosophila by modulating microtubule dynamics during meiosis. Issue 4 (11th June 2020) - Wormser, Ohad; Levy, Ygal; Bakhrat, Anna; Bonaccorsi, Silvia; Graziadio, Lucia; Gatti, Maurizio; AbuMadighem, Ali; McKenney, Richard J; Okada, Kyoko; El Riati, Saad; Har-Vardi, Iris; Huleihel, Mahmoud; et al.
Abstract : Background: Mutation in S-phase cyclin A-associated protein rin the endoplasmic reticulum ( SCAPER ) have been found across ethnicities and have been shown to cause variable penetrance of an array of pathological traits, including intellectual disability, retinitis pigmentosa and ciliopathies. Methods: Human clinical phenotyping, surgical testicular sperm extraction and testicular tissue staining. Generation and analysis of short spindle 3 ( ssp3 ) ( SCAPER orthologue) Drosophila CAS9-knockout lines. In vitro microtubule (MT) binding assayed by total internal reflection fluorescence microscopy. Results: We show that patients homozygous for a SCAPER mutation lack SCAPER expression in spermatogonia (SPG) and are azoospermic due to early defects in spermatogenesis, leading to the complete absence of meiotic cells . Interestingly, Drosophil a null mutants for the ubiquitously expressed ssp3 gene are viable and female fertile but male sterile. We further show that male sterility in ssp3 null mutants is due to failure in both chromosome segregation and cytokinesis. In cells undergoing male meiosis, the MTs emanating from the centrosomes do not appear to interact properly with the chromosomes, which remain dispersed within dividing spermatocytes (SPCs). In addition, mutant SPCs are unable to assemble a normal central spindle and undergo cytokinesis. Consistent with these results, an in vitro assay demonstrated that both SCAPER and Ssp3 directly bind MTs. Conclusions: Our results show that SCAPER null mutations block the entry into meiosis of SPG, causing azoospermia. Null mutations in ssp3 specifically disrupt MT dynamics during male meiosis, leading to sterility. Moreover, both SCAPER and Ssp3 bind MTs in vitro. These results raise the intriguing possibility of a common feature between human and Drosophila meiosis.